Nonlinear Calculation Method for One-Dimensional Compression of Soils - Alibrahim, Bashar; Uygar, Eris (Springer Heidelberg, 2022)
Soil settlement is an essential criterion in the design and performance assessment of geotechnical structures, often evaluated using results from one-dimensional compression test. However, assessment of the results from this test involves graphical methods, which produces inconsistent interpretations on the parameters to be used in design. The nonlinear compressibility curve is also subjected to bilinear idealization with divergence from the actual behavior at high stresses. In order to overcome these problems, a nonlinear mathematical formulation is developed to represent the soil compressibility with high precision over a wide range of stresses. The adequacy of the formulation is validated against a large and diverse dataset comprised of different geological materials, including undisturbed and reconstituted soils as well as stabilized soils. The proposed formulation is dependent on two fitting coefficients, which are defined in terms of commonly used compressibility parameters compression index, recompression index and preconsolidation pressure. A single expression is also derived to calculate soil settlement without numerical discontinuity. Finally, a method for evaluation of swelling pressure of soils is also developed using the parameters of the same mathematical formulation.
Keywords: One-dimensional compression; Compressibility parameters; Nonlinear settlement; Optimization; Swelling pressure